Unveiling local knowledge: a case study on inner development and sustainable transformation in rural areas - Christoph Schwenck; Jannis Pfendtner-Heise; Henrik von Wehrden (Discover Sustainability)
Abstract The concept of inner development serves as a strategic approach for advancing sustainable transformation and mitigating land consumption in rural areas. By employing an exploratory sequential design, this study analyses local knowledge from political and administrative actors within the district of Lüneburg, Germany. Through qualitative interviews we first identified 25 potential measures for facilitating the feasibility of inner development. Subsequently, utilising Q-methodology, five distinct factors were identified that represent shared clusters of participants’ opinions. Our findings reveal a spectrum of viewpoints, highlighting both consensus and divergence regarding measures to promote inner development. These findings were complemented by qualitative insights into barriers, which underscore the need for multi-level strategies that facilitate change at the local level while addressing systemic and cross-regional challenges. The integration of local knowledge emerges as essential for developing context-sensitive, place-based approaches that reflect the diverse characteristics of rural communities. In this context, we propose that the New European Bauhaus serves as a supporting framework, promoting a positive narrative around inner development and enhancing its potential for sustainability transformation. By recognising inner development as a holistic approach and aligning it with the Bauhaus initiative, rural communities are empowered to embrace integrative and sustainable solutions.